Dissociation of progeny vaccinia virus from the cell membrane is regulated by a viral envelope glycoprotein: effect of a point mutation in the lectin homology domain of the A34R gene. - Blasco, R (1993)
Vaccinia virus strains vary considerably in the amounts of extracellular enveloped virus (EEV) that they release from infected cells. The IHD-J strain produces up to 40 times more EEV than does the related WR strain and consequently generates elongated comet-shaped virus plaques instead of sharply defined round ones in susceptible monolayer cells under liquid medium. The difference in EEV formation is due to the retention of enveloped WR virions on the cell surface (R. Blasco and B. Moss, J. Virol. 66:4170-4179, 1992). By using WR and IHD-J DNA fragments for marker transfer and analyzing the progeny virus by the comet formation assay, we determined that gene A34R and at least one other gene regulate the release of cell-associated virions. Replacement of the A34R gene of WR with the corresponding gene from IHD-J increased the amount of EEV produced by 10-fold and conferred the ability to form distinctive comet-shaped plaques. Gene A34R encodes an EEV-specific glycoprotein with homology to C-type animal lectins (S.A. Duncan and G.L. Smith, J. Virol. 66:1610-1621, 1992). The nucleotide sequences of the A34R genes of WR and IHD-J strains differed in six positions, of which four were silent. One of the codon mutations (Lys-151-->Glu), which is located in the putative carbohydrate recognition domain, was sufficient to transfer a comet-forming phenotype to WR virus. These data indicate that the A34R-encoded glycoprotein is involved, through its lectin homology domain, in the retention of progeny virus on the surface of parental cells and raise the possibility that the protein also has a role in virus attachment to uninfected cells.